2014
DOI: 10.5688/ajpe787136
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effectiveness of Online Anaphylaxis Education for Pharmacists

Abstract: Objective. To evaluate the long-term effectiveness of an Australasian Society of Clinical Immunology and Allergy (ASCIA) anaphylaxis e-learning program compared to lectures or no training. Design. A controlled interrupted-time-series study of Australian pharmacists and pharmacy students who completed ASCIA anaphylaxis e-learning or lecture programs was conducted during 2011-2013. Effectiveness was measured using a validated test administered pretraining, posttraining, and 3 and 7 months after training. Assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…2013 -2018 (excluding any studies already reviewed by Salter and colleagues [6]) Year of publication on participants' practice and/or if the e-learning intervention resulted in patient benefit or an improved quality of care. Studies involving other health professionals/students, other pharmacy staff, faculty members or patients were not included, with the exception of one study where a control group of medical students received no training [9]. Studies using technologies that were based solely in a classroom (not remote) setting were excluded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2013 -2018 (excluding any studies already reviewed by Salter and colleagues [6]) Year of publication on participants' practice and/or if the e-learning intervention resulted in patient benefit or an improved quality of care. Studies involving other health professionals/students, other pharmacy staff, faculty members or patients were not included, with the exception of one study where a control group of medical students received no training [9]. Studies using technologies that were based solely in a classroom (not remote) setting were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Eight (14.3%) studies involved pharmacists [10][11][12][13][14][15][16][17], one (1.8%) involved pre-registration pharmacists [18], forty-six (82.1%) involved pharmacy undergraduate students and one (1.8%) involved both pharmacists and pharmacy students [9]. The number of participants ranged from eight in the smallest study [34], up to seven hundred and ninety-two in the largest [13].…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we could not determine whether the knowledge and understanding required to answer the CPD questions correctly were derived from the article or from other sources, making it difficult to conclude the direct impact of the CPD intervention on this area of pharmacy practice. Additionally, we could not evaluate the effect of the CPD article on increasing knowledge or long-term knowledge change, which would be better established through a randomized study, similar to the methodology used by Salter et al 40 Another limitation to this study was that the primary outcome was knowledge and application, not change in practice or patient outcomes. Tests of knowledge alone are insufficient to properly assess translation of knowledge and skills into practice.…”
Section: Discussionmentioning
confidence: 99%
“…While the clinical outcome from provision of emergency action plans is yet to be investigated in controlled studies, 7 educational training has been shown to result in more accurate recognition of symptoms of anaphylaxis by health professionals, 8 and to improve knowledge of FA and change practice in catering staff 9 . Finally, an evaluation of ASCIA pharmacist e‐training demonstrated improved knowledge after training compared with baseline or no training, and long‐term retention of knowledge 7 months after completion 10 …”
mentioning
confidence: 99%